Extracellular signal-regulated kinase (ERK) activation preserves cardiac function in pressure overload induced hypertrophy. (1st November 2018) - Mutlak, Michael; Schlesinger-Laufer, Michal; Haas, Tali; Shofti, Rona; Ballan, Nimer; Lewis, Yair E.; Zuler, Mor; Zohar, Yaniv; Caspi, Lilac H.; Kehat, Izhak
Abstract: Background: Chronic pressure overload and a variety of mediators induce concentric cardiac hypertrophy. When prolonged, cardiac hypertrophy culminates in decreased myocardial function and heart failure. Activation of the extracellular signal-regulated kinase (ERK) is consistently observed in animal models of hypertrophy and in human patients, but its role in the process is controversial. Methods: We generated transgenic mouse lines with cardiomyocyte restricted overexpression of intrinsically active ERK1, which similar to the observations in hypertrophy is phosphorylated on both the TEY and the Thr207 motifs and is overexpressed at pathophysiological levels. Results: The activated ERK1 transgenic mice developed a modest adaptive hypertrophy with increased contractile function and without fibrosis. Following induction of pressure-overload, where multiple pathways are stimulated, this activation did not further increase the degree of hypertrophy but protected the heart through a decrease in the degree of fibrosis and maintenance of ventricular contractile function. Conclusions: The ERK pathway acts to promote a compensated hypertrophic response, with enhanced contractile function and reduced fibrosis. The activation of this pathway may be a therapeutic strategy to preserve contractile function when the pressure overload cannot be easily alleviated. The inhibition of this pathway, which is increasingly being used for cancer therapy on the other hand, should be used with caution in the presence of pressure-overload. Highlights: ERK activation is consistently observed in animal models of hypertrophy and in human patients. We generated transgenic mouse lines with cardiac overexpression of intrinsically active ERK1. Activation of ERK results in an adaptive concentric hypertrophy. In pressure overload ERK activation reduces the fibrosis and preserves contractile function.